Evaluasi Uji ELISA dengan Serum Lapangan sebagai Crude Antigen di Bali - GM, Pratiwi Devi; Damriyasa, I.M.; Dharmawan, N.S. (Veterinary Science and Medicine Journal; Vol 2 No 1 (2014), 2014)
The purpose of this study was to evaluate the ELISA test using field serum and to determine the incidence rate of cysticercosis of T. saginata in Bali. Serum’s sample obtained from Bali cattle that slaughtered at the abattoir and Bali cattle owned by the farmers. The result of sera examination showed that 237 (87.7%) were positive of antibodies of cysticercus of T. saginata. Furthermore, as many as 90 (33.33%) of the 270 Bali cattles, their feces were also taken for examination of worm eggs. The results of stool examination showed that 80 (88.9%) were infected with trematodes and 14 (15.5%) were infected with a mixture of trematodes and nematodes. By comparing the results of ELISA and stool examination using the sensitivity and specificity approach or Table 2 x 2, the results showed that there was a cross-reaction between Cysticercus of T. saginata and trematode. Further effort to purify the antigen of cysticercus of T. saginata is still needed to improve its sensitivity and specificity.
Keywords: Bali cattle, ELISA, crude antigen, cysticercus of T. saginata